Prevalence of Coronary Artery disease in Patients undergoing Non Coronary Cardiac Surgery: A Single Center Study (Medico Legal Update, 2020)
Objectives: to evaluate the prevalence of significant coronary artery disease (CAD) in patients referred for open heart surgery for various valvular and non valvular etiologies.Methods and materials: a total of 160 patients (73 males and 87 females) were included in this study: old age, male gender, hypertension (HT), diabetes mellitus (DM), hyperlipidemia, smoking and left ventricular (LV) systolic dysfunction are recorded as risk factors for CAD. Of the 160 patients: 143 (89.4 %) have valvular disease (VHD) and 17 (10.6%) have non valvular disease. Patients with VHD were classified according to valve lesions into: mitral stenosis (MS), mitral regurgitation (MR), aortic stenosis (AS), aortic regurgitation (AR), tricuspid regurgitation (TR) and mixed valvular disease. Correlation between various types of valve diseases and CAD are assessed.Results: CAD were detected in 26.9% (43) of patients. Old age, HT, DM, hyperlipidemia and smoking were significantly correlated with CAD. CAD were more common in patients with VHD than non VHD. 25(50%) patients with AS have significant CAD (P value= 0.0001), in patients with MR: 8(12.7%) have significant CAD, while patients with MS and AR were have CAD in 15.1% and 25% respectively. Among patients with non valvular heart disease (17 patients): 13 patients have atrial septal defect and 4 patients have atrial myxoma. 3 patients (6.1%) have significant CAD (P value=0.2), one of them had HT, DM and smoker man presented with chest pain on exertion.Conclusion: Obstructive CAD were more common in patients with AS and MR and higher in patients with risk factors for CAD.